2022
DOI: 10.3390/machines10050315
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cell Concentration Change and Cell Aggregation Due to Cell Sedimentation during Inkjet-Based Bioprinting of Cell-Laden Bioink

Abstract: Recently, even though 3D bioprinting has made it possible to fabricate 3D artificial tissues/organs, it still faces several significant challenges such as cell sedimentation and aggregation. As the essential element of 3D bioprinting, bioink is usually composed of biological materials and living cells. Guided by the initially dominant gravitational force, cells sediment, resulting in the non-uniformity of the bioink and the decrease in the printing reliability. This study primarily focuses on the quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Xu et al investigated the piezoelectric-actuated bioprinting of cell-bearing alginate bioink directly into a crosslinking agent to develop cell-laden microspheres (Fig. 1 C) 32 . However, the current forms of DOD bioprinting are limited by inconsistent droplet volumes and negative effects on cell viability after dispensing at high pressures.…”
Section: Biofabrication Methods For Mini-tissues/organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al investigated the piezoelectric-actuated bioprinting of cell-bearing alginate bioink directly into a crosslinking agent to develop cell-laden microspheres (Fig. 1 C) 32 . However, the current forms of DOD bioprinting are limited by inconsistent droplet volumes and negative effects on cell viability after dispensing at high pressures.…”
Section: Biofabrication Methods For Mini-tissues/organoidsmentioning
confidence: 99%
“…( C ) Schematic illustration of inkjet bioprinting system containing several components including piezoactuator-attached inkjet nozzle, a waveform generator, a pneumatic controller, a bioink reservoir. Adapted with permission from 32 , copyright MDPI 2022. ( D ) (i) Schematical diagram and (ii) optical images of drop-on-demand bioprinting method.…”
Section: Figurementioning
confidence: 99%
“…Moreover, cell aggregation was observed using 0.5% (w/v) sodium alginate at 120 min printing time. Recently, Xu et al 45 investigated the effect of cell sedimentation on the cell concentration and cell aggregation within the bioink reservoir. It was reported that only within 40 min of printing time, almost all of the cells within the bioink containing 0.5% (w/v) sodium alginate have sedimented to the bottom, significantly increasing the cell concentration and facilitating cell aggregation.…”
Section: Introductionmentioning
confidence: 99%